2012
DOI: 10.1590/s1516-14392012005000116
|View full text |Cite
|
Sign up to set email alerts
|

Tensile properties of duplex UNS S32205 and lean duplex UNS S32304 steels and the influence of short duration 475 ºC aging

Abstract: Duplex stainless steels are high strength and corrosion resistant steels extensively used in the petrochemical and chemical industries. The aging at 475 °C for long periods of time provokes embrittlement and deterioration of corrosion resistance. However, short duration aging at 475 °C may be used as heat treatment to improve mechanical resistance with small decrease in the other properties. In this work the flow stress curves of lean duplex UNS S32304 and duplex UNS S32205 steels were modeled with Hollomon's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 11 publications
0
7
0
6
Order By: Relevance
“…Além disso, também foi possível observar que, após 1 h de envelhecimento, ocorreu aumento expressivo da dureza com praticamente ausência de perda da tenacidade. Estes resultados estão de acordo com os observados por Silva et al [13] e Albuquerque et al [14] em aços inoxidáveis duplex UNS S31803, que sugerem ser possível observar somente variação na dureza no estágio inicial da decomposição espinodal da fase α. Alguns autores afirmam ainda que tratamentos térmicos a 475ºC por curtos tempos podem ser benéficos para aços inoxidáveis duplex, pois aumentam a resistência mecânica da liga sem perda significativa de tenacidade [3]. A Figura 3 ilustra imagens de microscopia de força atômica e de microscopia de força magnética após conclusão da primeira etapa de preparação das amostras do aço na condição como recebido e após todos os envelhecimentos.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Além disso, também foi possível observar que, após 1 h de envelhecimento, ocorreu aumento expressivo da dureza com praticamente ausência de perda da tenacidade. Estes resultados estão de acordo com os observados por Silva et al [13] e Albuquerque et al [14] em aços inoxidáveis duplex UNS S31803, que sugerem ser possível observar somente variação na dureza no estágio inicial da decomposição espinodal da fase α. Alguns autores afirmam ainda que tratamentos térmicos a 475ºC por curtos tempos podem ser benéficos para aços inoxidáveis duplex, pois aumentam a resistência mecânica da liga sem perda significativa de tenacidade [3]. A Figura 3 ilustra imagens de microscopia de força atômica e de microscopia de força magnética após conclusão da primeira etapa de preparação das amostras do aço na condição como recebido e após todos os envelhecimentos.…”
Section: Resultsunclassified
“…Devido à sua combinação de boa resistência mecânica, boa resistência à corrosão e à corrosão sob tensão, seu uso tem crescido continuamente nas indústrias nuclear, química, de óleo e gás, de papel e celulose entre outras [2,3]. Apesar das interessantes características, a utilização destes aços é limitada a uma estreita faixa de temperaturas devido à sua susceptibilidade a precipitação de fases indesejáveis.…”
Section: Introductionunclassified
“…Spinodal decomposition in ferrite of CDSS during thermal aging is widely regarded as the primary mechanism of embrittlement [8][9][10][11][12]. Earlier studies indicated that long-term thermal aging caused the degradation in mechanical properties, such as impact properties, hardness, and tensile properties [13][14][15][16]. It was found that the impact toughness of CDSS decreased with an increasing aging time and the ductile-to-brittle transition in the impact fracture occurred after long-term thermal aging [17].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, values found in phase quantification can be influenced by the existing measurement techniques. Previous work [4,5] showed quantification of the ferrite volume fraction of duplex stainless steels using two different techniques: quantitative metallography after Beraha metallographic etching and magnetic measurements with the aid of a ferritoscope. The results showed considerable discrepancies between the values obtained by these techniques, and none of them are similar to the values calculated using ThermoCalc® software [4].…”
Section: Introductionmentioning
confidence: 99%